Tailoring the Chemical Potential of Crystal Growth Units to Tune the Bulk Structure of Nanocrystals. Issue 3 (1st September 2020) - Zhang, Jiawei; Du, Guifen; Li, Huiqi; Chen, Qiaoli; Kuang, Qin; Jiang, Zhiyuan; Xie, Zhaoxiong
Abstract: The intrinsic factors affecting the bulk structures of nanocrystallites are not well explored during crystallization. In this study, it is demonstrated that the chemical potential of growth units plays decisive role in governing the final structure of nanocrystals. It is found that the types of reaction vessels are able to vary the chemical potential of growth units, and make the Pt and Pd nanocrystals (NCs) unexpectedly evolve from the cyclic penta‐twinned to the single‐crystal nanostructures. In turn, it is concluded that the crystal growth units with lower chemical potential favor the formation of crystal nuclei with lower chemical potential during the nucleation. This new approach in tuning the bulk structures of NCs enriches the understanding of the crystallization process under supersaturated (nonequilibrium) condition, and would provide a general guidance for controlling nanocrystals with various thermodynamic forms. Abstract : Chemical potential of growth units is decisive in tuning the bulk structure of nanocrystals. The crystal growth units with lower chemical potentials prefer the formation of crystal nuclei with lower chemical potentials during the nucleation. Accordingly, nanocrystals with various thermodynamic forms can be expected by precisely controlling the chemical potential of growth units.